Pengaruh Harga dan Promosi Terhadap Loyalitas dalam Memilih Pembiayaan Akad Mudharabah Melalui Kepuasan Sebagai Variabel Intervening (Studi pada Nasabah Bank Syariah Indonesia Cabang Makassar Veteran): Pengaruh Harga dan Promosi Terhadap Loyalitas Transportasi Ojek Online Gojek di Makassar - Iryani; Sudirman; Abdullah, Wahidah (Study of Scientific and Behavioral Management, 2022)
ABSTRACT The aim of this study is to analyze and find out how much influence price and promotion have on customer loyalty in choosing mudharabah contract financing through customer satisfaction as an intervening variable. This research uses quantitative research using an explanatory approach. The results of this study indicate that price and promotion have a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer loyalty, while promotion has a negative and significant effect on customer loyalty and price and promotion have a positive and significant effect on customer loyalty through customer satisfaction at the Bank. Indonesian Sharia Branch Makassar Veterans Keywords: Price, Promotion, Loyalty and Satisfaction. and Mudharabah Agreement